Capital market reaction to equity private placement: The Malaysian experience 1999 - 2007 - Nordin, Norhafiza (Malaysia Finance Association, 2011)
This study investigates the announcement effect of 208 equity private placements in Malaysia using conventional event study for the period 1999 to 2007. This study is motivated by empirical findings that unlike public placements, private placements are associated with positive announcement effect. However, inconsistent with previous studies, we find zero announcement effect for Malaysian market. The results of this study also contribute to the existing literature by providing evidence that equity private placement in Malaysia does not support Wruck’s (1989) monitoring hypothesis and Hertzel and Smith’s (1993) information (certification) hypothesis. Cross-sectional analysis suggests that stock price reaction to the announcement of private placement can partly be explained by firm size, investment opportunity, change in ownership concentration and change in volume. While not ruling out other plausible explanations, it appears that the results of this study are the consequences of the regulation dictates that only two percent of issued shares may be granted to one placee.